Writing in the Real World: Integrating Contextual Teaching and Learning and Gamification to Improve Students’ Literacy - Hana, Putri (The Future of Education Journal, 2025)
This study aims to investigate the implementation of the Contextual Teaching and Learning (CTL) model and gamification in improving elementary school students’ writing skills. The main focus of this research is to explore how both approaches can be integrated to create a more engaging, relevant, and effective learning experience. This study employed a qualitative approach with a classroom action research (CAR) design conducted in two cycles, involving 30 fourth-grade students and two teachers. Data were collected through classroom observations, interviews, writing skill tests, student engagement observation sheets, and documentation in the form of photos and videos of learning activities. The data were analyzed using Miles and Huberman’s interactive analysis model. The results show that the integrated application of CTL and gamification significantly improved students’ writing quality and fluency, enhanced learning motivation, and increased active participation during the writing process. Students not only produced more structured and coherent texts but were also able to connect their writing ideas with real-life contexts and experiences. Gamification contributed to intrinsic motivation through points, badges, and challenges, while CTL helped students recognize the relevance of learning to everyday life. Overall, the integration of these two approaches proved effective in improving writing skills while fostering students’ cognitive, social, and metacognitive abilities. CTL and gamification can thus serve as innovative teaching strategies in writing instruction to create more meaningful and sustainable learning experiences.